Revitalisasi Pendidikan: Menyoal Format Nasionalisme Kita Jelang Indonesia Emas 2045 - Paturahman, Maman; Sudrajat, Yayan; Rejeki, Suyekti Kinanthi; Sari, Ni Wayan Ayu Permata (PT. LANCAR MEDIA KOMUNIKASI, 2024)
There is no independence of a nation without nationalism. The birth of a country and national passion are always built by a strong sense of nationalism. Nationalism will never be obsolete and will remain the identity of every child of the nation and become the pride of the nation whatever